Oxygraphis kumaonensis sp. nov. (Ranunculaceae) from Western Himalaya, India - Rai, Ishwari Datt; Rawat, Gopal Singh (Phytotaxa, 2015)
Oxygraphis kumaonensis I. D. Rai and G. S. Rawat, a new species from the alpine region of Western Himalaya is described and illustrated. Diagnostic features for identification, brief notes on the ecology and description of Type locality are given. The species is named after place of its occurrence, i.e., Kumaon, a well-known floristic sub-region in the state of Uttarakhand, India. Information on the distribution and conservation status of the new species is provided.